Rozwój rynku energii elektrycznej w Polsce w kontekście integracji z Unią Europejską - Graczyk, Andrzej; Jakubczyk, Zbigniew (Development of Electricity Market in Poland in Terms of European Integration, 2005)
The paper deals with the problems of adjusting Polish electricity market to the requirements of market liberalization (deregulation) according to the Directive 96/92/EC. The authors start with presenting current structures of the market concerned. They make an attempt at appraising whether and to what extent business entities acting within these structures show the willingness to create and observe the principles of liberal energy market, both in Poland and the EU. The paper also identifies barriers which may hamper Poland's participations in the European common energy market. A part of them ensues from the features of Polish electricity distribution system: the existence of long-term electricity purchase contracts between the state grid company (PSE) and power stations and small scale of transactions in the clearing market and electricity exchange. On the other hand, an impediment to the emergence of real electricity market in Poland may turn out to be a weak development of that market in the EU itself, differences in the level of market liberalization in specific EU countries and compulsory purchases of renewable energy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1056, s. 155-168